Peran Negara G20 dalam Percepatan Transisi Energi Baru Terbarukan (EBT) untuk Mewujudkan Ketahanan Energi Nasional - Rizky, Lucitania; Pratiwi, Tiffany Setyo; Wibawa, Adi; Achdiyana, Isna (Universitas Gadjah Mada, 2023)
ASBTRACT This research discussed international influences, especially G20 member countries in accelerating the national energy transition to realizing national energy resilience, according to the mandate of the established rules. The approach used in this study is an intermestic model approach which provides a pattern of the influence of international interests and global ideas in mapping the domestic political agenda, namely the energy transition as a priority issue. The research method used is a qualitative approach with data collection techniques and in-depth interviews with the Directorate General of Multilateral Cooperation, Ministry of Foreign Affairs of the Republic of Indonesia.The results of the study show that the acceleration of the Net Zero Emission (NZE) 2060 Roadmap is related to the intermestic idea that international support and assistance patterns have an impact on national energy resilence.